2019
DOI: 10.1096/fj.201901603rr
|View full text |Cite
|
Sign up to set email alerts
|

Using 17β‐estradiol heparin‐poloxamer thermosensitive hydrogel to enhance the endometrial regeneration and functional recovery of intrauterine adhesions in a rat model

Abstract: Mechanical damage or infection to the endometrium can lead to the formation of adhesions in the uterine cavity, which may result in reduced reproductive outcome and/ or pregnancy complications. The prognosis of this disease is poor due to few effective treatments and the complex environment of endometrium. Heparin-Poloxamer Hydrogel (HP hydrogel) is a nontoxic and biodegradable biomaterial, which has been commonly used as a sustained-release delivery system. In this study, we applied a miniendometrial curette … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Moreover, its therapeutic effect was associated with the inhibition of ER stress-induced apoptosis and the augmentation of the vascular endothelial growth factor (VEGF)-stimulated angiogenesis. The E2-HP hydrogel on the recovery of IUA was closely associated with the upregulation of kisspeptin through activating the ERK1/2 and MAPKs p38 pathways [ 54 ].…”
Section: Poloxamers In Endometrial Regenerative Medicinementioning
confidence: 99%
“…Moreover, its therapeutic effect was associated with the inhibition of ER stress-induced apoptosis and the augmentation of the vascular endothelial growth factor (VEGF)-stimulated angiogenesis. The E2-HP hydrogel on the recovery of IUA was closely associated with the upregulation of kisspeptin through activating the ERK1/2 and MAPKs p38 pathways [ 54 ].…”
Section: Poloxamers In Endometrial Regenerative Medicinementioning
confidence: 99%
“…Another bioengineering approach is the use of hydrogels, which are three-dimensional hydrophilic polymer networks (Hoffman, 2002) derived from hyaluronic acid (Liu et al, 2019;Kim, Park et al, 2019) or different poloxamers (Yang et al, 2017;Zhang et al, 2020), among other biomaterials. To enhance the synergies of this novel approach and other classical therapies, artificial hydrogels have been applied in several murine models together with other factors or cells.…”
Section: Hydrogelsmentioning
confidence: 99%
“…To enhance the synergies of this novel approach and other classical therapies, artificial hydrogels have been applied in several murine models together with other factors or cells. These combinations have been performed using estradiol embedded in an aloe-poloxamer (Yao et al, 2020) and a heparin-poloxamer hydrogel (Zhang et al, 2020) for restoring endometrium in rat models of intrauterine adhesions. Both studies reported improvement in the endometrial morphology status and a reduction in fibrosis, as well as the overexpression of cell proliferation and endometrial regeneration factors.…”
Section: Hydrogelsmentioning
confidence: 99%
“…Recovery of the uterine endometrium is facilitated by introduction of various biological substances that are able to stimulate regeneration of the tissue leading to restoration of reproductive capacity [14]. Type of biomaterial is an important factor in tissue engineering since it may provide structural support mimicking native uterine endometrial tissues [15]. The biomimetic should include a supporting layer and biologically active molecules.…”
Section: Endometrium Regeneration Using Surface-functionalized Hydrogelsmentioning
confidence: 99%